Solvent Systems and Their Selection in Pharmaceutics and Biopharmaceutics - Augustijns, Patrick; Brewster, Marcus; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2007)
Solvent systems are integral to drug development and pharmaceutical technology. This single topic encompasses numerous allied subjects running the gamut from recrystallization solvents to biorelevant media. The goal of this contribution to the AAPS Biotechnology: Pharmaceutical Aspects series is to generate both a practical handbook as well as a reference allowing the reader to make effective decisions concerning the use of solvents and solvent systems. To this end, the monograph was created by inviting recognized experts from a number of fields to author relevant sections. Specifically, 15 chapters have been designed covering the theoretical background of solubility, the effect of ionic equilibria and pH on solubilization, the use of solvents to effect drug substance crystallization and polymorph selection, the use of solvent systems in high throughput screening and early discovery, solvent use in preformulation, the use of solvents in bio-relevant dissolution and permeation experiments, solvents and their use as toxicology vehicles, solubilizing media and excipients in oral and parenteral formulation development, specialized vehicles for protein formulation and solvent systems for topical and pulmonary drug administration. The chapters are organized such that useful decision trees are included together with the scientific underpinning for their application. In addition, trends in the use of solvent systems and a balance of current views make this monograph useful to both the novice and experienced researcher and to scientists at all developmental stages from early discovery to late pharmaceutical operations.
Principles of Solubility -- Ionic Equilibria and the pH Dependence of Solubility -- Solvent Systems for Crystallization and Polymorph Selection -- Solubility Issues in Early Discovery and HTS -- Practical Aspects of Solubility Determination in Pharmaceutical Preformulation -- Biorelevant Dissolution Media -- Selection of Solvent Systems for Membrane-, Cell- and Tissue-Based Permeability Assessment -- The Use of Solubilizing Excipients and Approaches to Generate Toxicology Vehicles for Contemporary Drug Pipelines -- Solubilizing Vehicles for Oral Formulation Development -- Solubilizing Systems for Parenteral Formulation Development—Small Molecules -- Aqueous Solubilizing Systems for Parenteral Formulation Development—Proteins -- Non-Aqueous Systems for Formulation Development—Proteins -- Pharmaceutical Solvents as Vehicles for Topical Dosage Forms -- Pharmaceutical Solvents for Pulmonary Drug Delivery.
Keywords: Pharmacology; Programming languages (Electronic computers).; Pharmacology/Toxicology.; Programming Languages, Compilers, Interpreters